Bone marrow mesenchymal stem cell-derived exosomes attenuate D-GaIN/LPS-induced hepatocyte apoptosis by activating autophagy in vitro - Zhao S; Liu Y; Pu Z (Drug Design, Development and Therapy, 2019)
Shuxian Zhao,1,2,* Yan Liu,2,* Zenghui Pu21Medical College of Qingdao University, Qingdao 266071, Shandong, People’s Republic of China; 2Department of Infectious Disease, Affiliated Yantai Yuhuangding Hospital of Qingdao University, Yantai 264000, Shandong, People’s Republic of ChinaCorrespondence: Zenghui PuDepartment of Infectious Disease, Affiliated Yantai Yuhuangding Hospital of Qingdao University, Yantai 264000, Shandong, People’s Republic of ChinaTel +86 1 861 505 6980Email 18615056980@163.com*These authors contributed equally to this workBackground: Acute liver failure is an inflammation-mediated hepatocyte injury. Mesenchymal stem cell (MSC) transplantation is currently considered to be an effective treatment strategy for acute liver failure. Exosomes are an important paracrine factor that can be used as a direct therapeutic agent. However, the use of bone marrow mesenchymal stem cell-derived exosomes (BMSC-Exos) in the treatment of acute liver failure has not been reported.Purpose: Here, we established a model of hepatocyte injury and apoptosis induced by D-galactosamine and lipopolysaccharide (D-GalN/LPS) to study the protective effect of BMSC-Exos on hepatocyte apoptosis, and further explored its protective mechanism.Methods: BMSC-Exos was identified by transmission electron microscopy (TEM), nanoparticle tracking analysis (NTA) and Western blot. Laser confocal microscopy was used to observe the uptake of Dil-Exos by hepatocytes. D-GalN/LPS-induced primary hepatocytes were pretreated with BMSC-Exos in vitro, and then the cells were harvested. The apoptosis of hepatocytes was observed by TUNEL staining, flow cytometry and Western blot. Electron microscopy and mRFP-GFP-LC3 and Western blot was used to observe autophagy.Results: BMSC-Exos increased the expression of autophagy marker proteins LC3 and Beclin-1 and promoted the formation of autophagosomes. After BMSC-Exos treatment, the expression levels of the proapoptotic proteins Bax and cleaved caspase-3 were significantly decreased, while the expression level of the anti-apoptotic protein Bcl-2 was upregulated. However, when the autophagy inhibitor 3MA was present, the effect of BMSC-Exos on inhibiting apoptosis was significantly reversed.Conclusions: Our results showed for the first time that BMSC-Exos had the potential to reduce hepatocyte apoptosis after acute liver failure. In particular, we found that BMSC-Exos attenuated hepatocyte apoptosis by promoting autophagy.Keywords: bone marrow mesenchymal stem cells, exosomes, D-GalN/LPS, apoptosis, autophagy, acute liver failure